Memory and medication compliance in young and elderly adults - Sullivan, Trevor (My University, 2000)
Poor medication compliance can result in reduced therapeutic benefits and a need for additional medical services (Putnam et al., 1984). The American Association of Retired Persons (1984) estimates that older adults consume an average of 3 or more medications daily. Poor medication compliance in elderly adults may be due to a decline in cognitive abilities (Park & Kidder, 1996). The present study was conducted to detemriine if poor medication compliance among elderly adults is associated with declining cognitive abilities. Older adults were contrasted with young adults on (a) their ability to adhere to a complex, pseudo-medication regimen for 4 weeks, and (b) subjective ratings of their medication compliance. Growth curve analyses revealed no group differences in self-reported compliance or change in self-reported ratings over time. Older adults demonstrated better medication compliance, as well as greater improvement in compliance over the 4 weeks. The results suggest that healthy older adults can successfully adhere to a complex medication regimen. Thus, other factors besides cognitive ability may be implicated in poor medication compliance by elderly adults.
Keywords: Patient compliance; Memory in old age; Aged Medical care